New tetradentate N, O-hybrid phenanthroline-derived organophosphorus extractants for the separation and complexation of trivalent actinides and lanthanides. Issue 18 (26th July 2022) - Yang, Xiao; Wang, Shihui; Xu, Lei; Yan, Qiang; Xu, Chao; Matveev, Petr; Lei, Lecheng; Xiao, Chengliang
Abstract : Comparison of the extraction and separation properties between two novel phenanthroline-derived organophosphorus ligands, Et-Ph-BPPhen and Et-Ph-PIPhen. Abstract : Phenanthroline-based tetradentate ligands with hard–soft donors have been the hotspots for the selective separation of minor actinides from lanthanides. Most of the previous studies closely focused on the impact of the side substituents or different skeletons on the extraction and complexation properties of ligands towards f-elements. Few strategies have been used to modify the hard O-donor atoms. In this work, two new tetradentate N, O -hybrid organophosphorus ligands, Et-Ph-BPPhen (L1 ) and Et-Ph-PIPhen (L2 ), were synthesized and employed to investigate the impact of the charge properties of O donor atoms. Their extraction properties and complexation behaviours with trivalent actinides and lanthanides were thoroughly studied through solvent extraction, 1 H/ 31 P NMR titration, UV-vis titration and X-ray single-crystal diffraction measurement. It was found that L2 showed a better extraction property and selective separation ability than L1 . Through the 1 H/ 31 P NMR spectra titration, only 1 : 1 metal-to-ligand complexes of two ligands (L1 and L2 ) with La(NO3 )3 were formed. And both 1 : 1 and 1 : 2 species were formed for Lu(NO3 )3 . The UV-vis titration revealed that both log β values of EuL1 (6.99 ± 0.04) and Eu(L1 )2 (12.21 ± 0.10) were smaller than those of EuL2 (7.04 ± 0.04) and Eu(L2 )2 (12.56 ± 0.08), which was consistent with the extraction results. The stability constants of 1 : 1 complexes increased along with the lanthanide contraction (from La(NO3 )3 to Lu(NO3 )3 ). The single-crystal structures of the complexes of L1 and L2 with lanthanides (La(NO3 )3, Eu(NO3 )3 and Lu(NO3 )3 ) were obtained. The results of the extraction and UV-vis titration were confirmed from the average distances of Eu–OL (L1 > L2 ). As reasonable estimators of selectivity factors, average distances of Eu–NL displayed a particular trend (L2 < L1 ), which corresponded to the pattern of SF (L2 > L1 ). Finally, for a series of crystals concerned with L1, the coordination numbers (CNs) reduced along with the lanthanide contraction. These results indicate that the separation ability could be improved by modifying the O donor atoms and phosphinate ligands may be an alternative for the separation of actinides from lanthanides.